ANALYSIS OF FACTORS AFFECTING STUDENTS OF ACCOUNTING STUDENTS USING FEB USU IN THE ERA OF ASEAN ECONOMIC AFFAIRS (MEA) WITH OPPORTUNITIES AND MEAS CHALLENGES FOR ACCOUNTING INDONESIA AS A MODERATING VARIABLE - Syahlina, Maya (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to examine and to analyze the Ethical Competency, Knowledge Competency, Capability Competency, Respect About Human Right and Value, Analysis Competency and Students Working Interest influence simultaneously and partially on Readiness Accounting Students FEB USU in the face of AEC (ASEAN Economic Community) as well as to determine whether the AEC Opportunities for Accountants in Indonesia and Challenges MEA for Accountants in Indonesia may moderate the relationship between Ethical Competency, Knowledge Competency, Capability Competency, Respect About Human Right and Value, Analysis Competency and Students Working Interest with the Student Readiness Accounting FEB USU in the face of the MEA. This research is associative causal research using primary data. The research population amounts to 225 students who are students of the seventh semester accounting (year in 2013). The sampling technique is using simple random sampling method with sloven formula for determining the number of samples. The analytical tool used in this study using multiple regression analysis. Based on test results simultaneously, the size of The objective of the research was to examine and to analyze the Ethical Competency, Knowledge Competency, Capability Competency, Respect About Human Right and Value, Analysis Competency and Students Working Interest in a significant effect on the readiness of Accounting Students FEB USU in the face of the AEC. Partially, this study found that each independent variable (Ethical Competency, Knowledge Competency, Capability Competency, Respect about Human Right and Value, Analysis Competency and Students Working Interest) partially significant positive effect on the readiness of Accounting Students FEB USU in the face of the AEC. Variable Opportunities AEC for Indonesian Accountants and Challenges MEA for the Indonesian Accountants cannot moderate the relationship between the variables of Ethical Competency, Knowledge Competency, Capability Competency, Respect About Human Right and Value, Analysis Competency and Students Working Interest in a significant effect on the readiness of Accounting Students FEB USU in the face AEC.